Calculate exact integrals in the visual basic window of excel - Nodira Sharifovna Khodjayeva; Muslimakhon Tokhirboyevna Yakhyayeva (International Journal on Orange Technologies, 2021)
A graphical view of the exact integral is shown and the execution is shown in the Visual basic window of Excel